"Open the Gates Mek We Repatriate": Caribbean slavery, constructivism, and hermeneutic tensions. Issue 2 (20th June 2014) - Shilliam, Robbie
Abstract : Constructivism has inherited a hermeneutic tension from the sociology of knowledge tradition regarding a strong ontological proposition that all social beings interpret their reality and a qualified epistemological proposition that some social beings are better able to interpret the reality of others. This article focuses on the politics of knowledge production that arise from this tension, namely that a privileged group, the 'scholastic caste', possesses the power to de-value the explanations of 'lay' groups' experiences by deeming them to be insufficiently 'scientific'. The article explores these politics by addressing the meaning of the abolition of and emancipation from Atlantic slavery, a case study popularly used in constructivist literature. Noting the absence of engagement by constructivists with the 'lay' interpretations of enslaved Africans and their descendants, the article explores a hermeneutical position developed by the Jamaican sociologist and novelist, Erna Brodber, which directly addresses these tensions.